On the wasp-mimicking sharpshooter genus Propetes Walker, 1851 (Hemiptera: Cicadellidae: Cicadellinae): description of a new species, proposal of a new synonymy, and distributional notes - Prando, Jádila Santos; Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda (Zootaxa, 2017)
The Neotropical genus Propetes Walker, 1851 currently includes three species recorded from Brazil and Guyana that share morphological characteristics related to wasp-mimicking behavior. A revision of available material of Amazonian Propetes was conducted, and a new species, P. sakakibara sp. nov., is described and illustrated herein based on males from Brazil, Peru, and Venezuela. Based on the association of males and females from Pará State (Brazil), a synonymy is proposed between P. triquetra (Fabricius, 1803) (previously known only from males) and P. compressa Walker, 1851 (previously known only from females). The female genitalia of P. triquetra is redescribed and illustrated in detail. Observation of bluffing display behavior is reported for the first time for the genus, in P. schmidti. A key to all species included in Propetes, based on males and females, and a map of distribution of Propetes species are provided, including new records of the genus from French Guiana, Peru, and Venezuela.